Effect of full-fat corn germ and Vitamin E on finishing performance and carcass characteristics of beef heifers - Montgomery, Sean P.; Sindt, J.J.; Greenquist, M.A.; Good, E.J.; Loe, E.R.; Sulpizio, M.J.; Kessen, T.J.; Drouillard, James S.; Depenbusch, Brandon E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eight hundred eighty-eight crossbred beef heifers weighing 837 lb were used in a 105- day finishing study to evaluate full-fat corn germ as a lipid source and added vitamin E in finishing diets containing steam-flaked corn. Treatments were arranged in a 2 × 4 factorial and consisted of finishing diets formulated to provide no added fat (Control), 4% tallow (Tallow), or 10% or 15% full fat corn germ on a dry matter basis (10%FFG and 15%FFG, respectively) with or without 2000 IU of additional vitamin E per heifer daily. No fat × vitamin E interaction was detected. Fat addition decreased (P<0.01) dry matter intake and tended (P<0.09) to improve gain efficiency, but marbling score and the number of carcasses grading USDA Choice were decreased by fat additions (P<0.01). Tallow and 10%FFG yielded similar finishing performance and carcass characteristics. Increasing full fat corn germ led to linear decreases (P<0.05) in dry matter intake, average daily gain, final body weight, and hot carcass weight, as well as marbling score and the number of carcasses grading USDA Choice. Gain efficiency was increased by addition of full fat corn germ at 10% of the diet, but not at 15% of the diet. Addition of full fat corn germ to the diet tended (linear, P<0.06) to decrease the incidence of liver abscesses. Addition of vitamin E did not affect finishing performance (P>0.12). This study suggests that full fat corn germ can serve as a supplemental lipid source for finishing cattle. Responses to 10% full fat corn germ were similar to those obtained when an equal amount of fat from tallow was incorporated into the diet.
Keywords: Beef; Vitamin E; Full-fat corn germ; Finishing performance; Carcass characteristics; Heifers